Quantification of Sensorimotor Skills and Psychophysiological Activation in Deaf Subjects Using Musical Stimuli - Osornio García, Fernando Uristy; Martínez Luna, Miguel Alberto; Guerrero Arenas, Coral Italú; Hernández Santana, Guillermo; Borne, Leonardo (Academia Journals, 2022)
Musical activities have been shown to be effective tools for the acquisition of sensorimotor (SMS) and cognitive skills, especially in deaf subjects. The aim of this research was to compare the SMS and psychophysiological state of 11 Deaf adult volunteers (27±9.3 years old) with respect to a group of 18 hearing (30.18±10.22 years old). SMS was explored using a mobile application that plays a specific rhythm while the subject identifies its respective pattern. The psychophysiological state (PsyS) was assessed by quantifying changes in indices derived from the processing of heart rate variability (HRV) and electrodermal activity (EDA) signals. SMS was explored using a mobile application that plays a specific rhythm while the subject identifies its respective pattern. At the same time, we quantify changes in PsyS. We identified that changes in the PsyS are most sensitively detected by indices derived from EDA signal analysis.
Pilot Study in deaf people
Keywords: Sensorimotor skills; Deaf people; Musical tasks; Biosignals; Heart Rate Variability; Electrodermal Activity